The influence of digital leadership, organizational communication, organizational culture, and emotional intelligence on teacher performance - Siskawati, Garina; Hendra, Robi; Habibi, Akhmad (Indonesian Journal of Educational Development (IJED), 2025)
This study aims to ascertain the ways in which organizational communication, organizational culture, digital leadership, and emotional intelligence impact teacher effectiveness. This study was conducted due to the fact that factors such as limitations in technology utilization, lack of organizational communication, unsupportive work culture, and low emotional intelligence still cause gaps in teacher performance. This study makes use of Smart-PLS.4 data analysis tools and quantitative approaches. This study collected data using an online questionnaire/survey using Google Forms. The sample size calculator was used as the sampling method. The population in this study was 1,525 Teachers, and the sample in the final result there were 342 respondents. The results of the study indicate that communication, organizational culture, digital leadership, and emotional intelligence all have an impact on how effective teachers are. The study recommends that principals should strengthen their digital leadership, teachers should improve their emotional intelligence, schools should build a strong culture of cooperation, and organizational communication should be improved through transparency and the use of technology. Future researchers are advised to expand the variables and approaches to make the results more comprehensive.